Case report: Long remission and survival following immunotherapy in a case of pulmonary pleomorphic carcinoma - Wang, Tongshan; Chen, Muyang; Wang, Anpeng; Zhang, Hao (Frontiers in Immunology, 2024)
In 2020, we reported on a case involving a 68-year-old male patient with a rare instance of pulmonary pleomorphic carcinoma exhibiting high PD-L1 expression. The patient experienced significant therapeutic success with the use of camrelizumab, achieving partial tumor remission. Following the publication of that report, the patient continued on camrelizumab at a dose of 200 mg/dl for 27 cycles, subsequently transitioning to a combination of camrelizumab and bevacizumab for eight cycles. Due to elevated blood pressure, the regimen was adjusted back to monotherapy with camrelizumab. As of July 9, 2024, the patient remains alive with a satisfactory quality of life. This follow-up report, coupled with a review of the literature from 2021 to 2024 on pulmonary pleomorphic carcinoma and its immunotherapeutic approaches, aims to present new insights and innovative strategies for treating this rare form of cancer.